2014
DOI: 10.1159/000354845
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds and Fatigue in Stroke

Abstract: Background and Purpose: Poststroke fatigue (PSF) is a frequent and persistent problem in stroke survivors. The neuroanatomical model of PSF remains unclear. This study examined the association between PSF and cerebral microbleeds (CMBs). Methods: The sample comprised 199 patients with acute ischemic stroke. A psychiatrist who was blind to the subjects' radiological data administered the Chinese version of the Fatigue Severity Scale. PSF was defined as a Fatigue Severity Scale score of 4.0 or more. The location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Some authors investigated the difference in incidence of fatigue based on type of lesion. Patients with large vessel stroke experienced greater fatigue than small vessel involvement,59 while other studies report an association with cerebral microbleeds 60. Those with stroke reported greater fatigue than transient ischaemic attack (TIA) despite minimal impairment 14.…”
Section: Mechanisms Of Psfmentioning
confidence: 99%
“…Some authors investigated the difference in incidence of fatigue based on type of lesion. Patients with large vessel stroke experienced greater fatigue than small vessel involvement,59 while other studies report an association with cerebral microbleeds 60. Those with stroke reported greater fatigue than transient ischaemic attack (TIA) despite minimal impairment 14.…”
Section: Mechanisms Of Psfmentioning
confidence: 99%
“…Twenty-five studies found that PSF was associated with greater disability and dependency [ 20 , 22 , 24 , 25 , 29 , 32 , 33 , 36 , 38 , 43 45 , 48 , 52 54 , 57 , 60 , 62 , 64 , 65 , 68 , 71 73 ], even though the association seems to be mediated by depression [ 74 ] and was not detected in 15 studies [ 5 , 19 , 21 , 23 , 31 , 42 , 46 , 48 50 , 56 , 61 , 67 , 69 , 75 ]. PSF was associated with less return to work (and particularly to a return to full-time work) soon or long after the stroke in seven studies [ 22 , 29 , 43 , 44 , 46 , 76 , 77 ] but not in another study [ 64 ].…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
“…Fatigue affects patients both physically and emotionally and is considered the most important bio-alert in human health [1]. Fatigue is associated with various types of neurological diseases such as multiple sclerosis (MS) [2,3], Parkinson's disease [3,4], stroke [3,5,6], and epilepsy [3,7,8]. Epilepsy is a common neurological disease and is the second most commonly reported disorder of the central nervous system in the world [9].…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy affects all aspects of daily life and uncontrolled seizures can lead to irreversible brain damage [10]. Studies have shown that patients with epilepsy experience a lower quality of life than patients with other chronic diseases such as asthma or diabetes [6,11]. According to the current literature, the frequency of fatigue in patients with PNES is higher than that in normal individuals, which can lead to a low quality of life in these patients [12,13].…”
Section: Introductionmentioning
confidence: 99%